2009
DOI: 10.21307/ijssis-2017-340
|View full text |Cite
|
Sign up to set email alerts
|

LF Indoor Location and Identification System

Abstract: In this paper, a low-frequency RFID location system based on a matrix of quad antennae placed under a floor surface is described. A prototype system was used for parameterisation and feasibility tests. The results show that it is possible to build a location system using floor quad antennae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Monitoring a subject in bed can reduce the falling incidents or going into the toilet as a huge number of fallings occur in such conditions 6 . Several ongoing research works have been reported [7][8][9][10][11][12][13] giving a comprehensive description of the existing such systems. Some of such monitoring systems include video/ camera, passive infrared sensors (PIR), motion sensors, Doppler sensors, radars, capacitive sensors, floor sensors, and so on as listed in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring a subject in bed can reduce the falling incidents or going into the toilet as a huge number of fallings occur in such conditions 6 . Several ongoing research works have been reported [7][8][9][10][11][12][13] giving a comprehensive description of the existing such systems. Some of such monitoring systems include video/ camera, passive infrared sensors (PIR), motion sensors, Doppler sensors, radars, capacitive sensors, floor sensors, and so on as listed in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…NFI sensor plates are surrounded with antenna loops that can be used to track RFID tags. With the RFID system, people can be both located and identified [10]. However, the RFID tracking is not as accurate as the NFI localization [39].…”
Section: Introductionmentioning
confidence: 99%
“…In this study we present a method which combines the use of a passive system with high accuracy [9,10] and an active system providing the identification [33]. The advantage of the proposed method is that the transponder is not disturbed by clothing, body shading, or being placed in a wallet or briefcase, unlike transponders using ultrasound, visible light, or IR.…”
mentioning
confidence: 99%
“…The idea and the concept have been described in detail in our earlier work [33]. The RFID system uses quad antennas, which are placed on the same elements as the NFI sensor electrodes and active RFID transponders [31].…”
mentioning
confidence: 99%
See 1 more Smart Citation